Hallucination experienced by the governess the turn of the screw - Hartini, Sri; , Prof. Dr. C. Bakdi Sumanto; , Dr. M. Thoyibi, M.S (2014)
The study is talking about Hallucination. The problem of this study is how hallucination reflected in Henry James' The Turn of The Screw. It uses psychological and sociological perspectives. Psychologically, the objectives of this study are presenting an analysis of the symptoms, the causes and effects of hallucination experienced by the governess. Besides, it also analyzes the sociological factor that describes the relationship of Henry James' The Turn of The Screw and social reality of English society at the end of 19th century; and to reveal the author's criticism at Henry James' The Turn of The Screw. The object of this study is Henry James' The Turn of The Screw novel. This research employs a qualitative approach that has two types of data sources, namely primary and secondary data. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The findings of the research based on the psychological analysis reveal the symptoms of hallucination experienced by the governess which are feeling anxious, seeing the apparitions, hearing some voices, feeling afraid, day dreaming, screaming, and talking to oneself, and the types of hallucination experienced by the governess which are auditory hallucination, visual hallucination, olfactory hallucination and mood-incongruent hallucination. The causes of hallucination experienced are her poverty, her low education, her too much responsibility, her repressed and unfulfilled sexual desire. And the effects of hallucination found are the governess insanity and over protective to the children. In addition, based on the sociological analysis, it is apparent that there is a strong relation between this novel and the social reality in England in the 19th century. And, the author criticizes about unequal social status and gender. The findings of this research are expected to give a wider horizon about hallucination, and also can add and enrich the knowledge about literature product. Furthermore, it will give some fresh ideas for further study in this research